Casa d'O Brasileiro. Estilo artístico e arquitectónico de sua época - Felipe Ramos de Matos (2021)
The present work results from the theme of the dissertation "Casa d'O Brasileiro": it is a study whose objective is to understand and analyze the house of a Portuguese stereotype who, after having made a fortune in Brazil, returns to Portugal to build his heritage, between the 19th and 20th centuries in the North of Portugal - designated or denominated at the time as "Brazilian". After an etymological observation necessary to understand the concepts of the discourse, we will look at relevant texts for understanding what is called Casa d'O Brasileiro, its geographical, anthropological and cultural integration of authors such as Domingo Tavares (1939-) and Paula Torres Peixoto (1963-), in their books such as: "Casas de Brasileiro" and "Palacetes de Brasileiros in Porto 1850-1930". Drawing parallels in the theories of other authors, such as Françoise Choay (1925-) and Fernando Távora (1923-2005). In the first part, the work is staggered to understand the meaning of the term Casa d'O Brasileiro and its ambiguities, trying to understand what are the characteristics inherent to the act of designing those residences through the following topics: Form, Function and Structure - architectural elements that analyze transversely in each specific case. Through a historical analysis of the heterogeneous morphologies of the houses under study, we will understand what defines the "Casa d'O Brasileiro". And consequently to know what are the differences that distinguish them from the constructions of that same time, namely the bourgeois houses. In the second part, we study a case study that consists of the analysis of three houses designed by the Architect José Marques da Silva (1869- 1943), for the "Brazilian" businessman Joaquim Soares da Silva Moreira (1843-1908). The owner builds, almost simultaneously, his houses in the city of Porto: the first house is built in 1903 on Rua de Dom João IV, and the second is located on the same street in the corner with Rua Conde Rodolfo de Araújo in the year of 1904, already the third house, it is a semi-detached beach residence, located at Rua de Gondarém No. 680, in 1908. In this way, it is interesting to understand that the three houses, located in three different sites, belong to the same Architect for the same developer. Even so, the design of the houses presents a different design according to their use (residential or laser) and the location (historic center and mouth), maintaining the heterogeneous style of "Casa d'O Brasileiro"